Design of an amphiphilic hyperbranched core/shell-type polymeric nanocarrier platform for drug delivery - ALARÇİN, EMİNE (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2020)
An amphiphilic core/shell-type polymer-based drug carrier system (HPAE- PCL-b-MPEG), composed of hyperbranched poly(aminoester)-based polymer (HPAE) as the core building block and poly(ethylene glycol)-b-poly(epsilon-caprolactone) diblock polymers (MPEG-b-PCL) as the shell building block, was designed. The synthesized polymers were characterized with FTIR, H-1 NMR, C-13 NMR, and GPC analysis. Monodisperse HPAE-PCL-b-MPEG nanoparticles with dimensions of <200 nm and polydispersity index of <0.5 were prepared by nanoprecipitation method and characterized with SEM, particle size, and zeta potential analysis. 5-Fluorouracil was encapsulated within HPAE-PCL-b-MPEG nanoparticles. In vitro drug release profiles and cytotoxicity of blank and 5-fluorouracil-loaded nanoparticles were examined against the human colon cancer HCT116 cell line. All results suggest that HPAE-PCL-b-MPEG nanoparticles offer an alternative and effective drug nanocarrier system for drug delivery applications.
Keywords: Hyperbranched polymer; poly(aminoester); nanoparticle; drug delivery; 5-fluorouracil; SOLID-LIPID NANOPARTICLES; CHITOSAN MICROSPHERES; SUSTAINED-RELEASE; PEG; OPTIMIZATION; 5-FLUOROURACIL; COPOLYMERS; MICELLES; CARRIERS; DENDRIMERS